If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m * m) + -25n * 25n = 0 Multiply m * m (m2) + -25n * 25n = 0 m2 + -25n * 25n = 0 Reorder the terms for easier multiplication: m2 + -25 * 25n * n = 0 Multiply -25 * 25 m2 + -625n * n = 0 Multiply n * n m2 + -625n2 = 0 Solving m2 + -625n2 = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '625n2' to each side of the equation. m2 + -625n2 + 625n2 = 0 + 625n2 Combine like terms: -625n2 + 625n2 = 0 m2 + 0 = 0 + 625n2 m2 = 0 + 625n2 Remove the zero: m2 = 625n2 Simplifying m2 = 625n2 Take the square root of each side: m = {-25n, 25n}
| 4(9-15y+6.25y^2)+16y^2=20(3-2.5y)+4y-19 | | (x*x)+3x-40=0 | | 36-60y+25y^2+16y^2-60+50y-4y+19=0 | | 6x+32=2x-8 | | 41y^2-14y-5=0 | | (4*-2)+13-6=0 | | (x*x)-33x=0 | | (38+x+50)/3=50 | | (x-x)-33x=0 | | -30-10x=56-24x | | 6a-5=3a-8 | | (x*2)-33x=0 | | x-33x=0 | | a+2b+3c=150 | | -18-[-4-(-8)]= | | 2x^2+12x+46=0 | | 200+12.5x=25x+25 | | 28/14 | | 47/x=-8 | | 2+7(3-2e)=7-2(6-3e) | | 5=2-5x | | 35(2x+12)=7(x-4)+3x | | 4x+3-x-3/2x+5 | | 1+3=0 | | 4x+3+x-3/2x+5 | | 3x*2x-1=18*6 | | 19x+3(4x+9)=-6x-38 | | 7(2a-5)=-21 | | -x+27=-6.8 | | 5(4x+8)=120 | | 8(6+2f)=128 | | 5(6y-2)=20 |